Efficacy of carbomer sodium hyaluronate trehalose vs hyaluronic acid to improve tear film instability and ocular surface discomfort after cataract surgery - Caretti, L (Clin Ophthalmol, 2019)
PURPOSE: To evaluate the effects of carbomer sodium hyaluronate trehalose (CHT) and sodium hyaluronate eye drops on tear film stability and ocular discomfort after cataract surgery. SETTING: Santa Maria della Misericordia Hospital, Rovigo, Italy. DESIGN: Prospective randomized case-control study. PATIENTS AND METHODS: This study enrolled sixty patients scheduled for unilateral cataract surgery. After phacoemulsification, subjects received carbomer sodium hyaluronate trehalose (trehalose group) or sodium hyaluronate tears (HG group) substitute and were assessed through objective (break up time, corneal and conjunctival staining) and subjective (OSDI questionnaire) clinical evaluations after a two times a day topical administration. Outcome measures were collected preoperatively (baseline), one week (day 7) and 1 month (day 30) after surgery. Finally, each patient was asked to give his personal treatment satisfaction score. RESULTS: Trehalose group showed a steeper break up time (BUT) increase compared to patient treated with hyaluronic acid (P<0.001). OSDI questionnaire presented a opposite trend, trehalose patients evidenced a significantly major improvement (P<0.001), and in seven days mean values reduced by more than three times. Fluorescein staining reduction was documented with both treatments, although there was no statistically significant difference between groups. Finally CHT resulted in a significantly greater global satisfaction score (P<0.001). CONCLUSIONS: CHT was effective and well tolerated in reducing dry eye disease symptoms and improving the clinical outcome after cataract surgery. On some parameters (BUT, OSDI), this new formulation was more effective than commonly used sodium hyaluronate in treating ocular irritation and tear film alterations.